Chemical Modification of Bacterial Cellulose for the Development of an Antibacterial Wound Dressing - Orlando, Isabel; Basnett, Pooja; Nigmatullin, Rinat; Wang, Wenxin; Knowles, Jonathan C.; Roy, Ipsita (Frontiers in Bioengineering and Biotechnology, 2020)
Bacterial cellulose is a bacterially derived polymer with great potential for application in wound healing due to its innate properties such as high biocompatibility and biodegradability. In addition to this, it is naturally biosynthesized by bacteria as a hydrogel, which makes it an optimal substrate for application on dry wounds, where additional moisture is required to facilitate the healing process. However, this polymer lacks antibacterial properties. As bacterial infections are becoming increasingly common and difficult to treat due to antimicrobial resistance, it is of crucial importance to develop strategies for the modification of cellulose to ensure protection against bacterial contamination. In this study, a green-chemistry approach was proposed for the functionalization of cellulose to introduce antibacterial functional groups. Two different active agents were used for the covalent derivatization of the hydroxyl groups of glucose using a heterogeneous reaction in basic aqueous conditions. The modified material was chemically and mechanically characterized through solid state techniques and rheological measurements. A biological assessment was then carried out both using bacterial cells and human keratinocytes. It was observed that the functionalization performed induced a reduction of approximately half of the bacterial population within 24 hours of direct contact both against Staphylococcus aureus subsp. aureus Rosenbach 6538P™ Escherichia coli (Migula) Castellani and Chalmers ATCC® 8739™ strains. In parallel, cytotoxicity studies performed on keratinocytes (HaCaT cell line) showed over 90% of cell viability for up to 6 days of direct contact with the samples. The morphology of the cells was also visually evaluated, and no significant difference was noted as compared to the control. Finally, the in vitro scratch assay evidenced good wound closure rates in the presence of both unmodified and modified cellulose. Overall, the modified hydrogel showed promising features, confirming its potential as an alternative substrate to develop a green, antibacterial and biocompatible wound dressing.